The great India demonetization - Lahiri, Amartya (The Journal of Economic Perspectives)
On November 8, 2016, India demonetized 86 percent of its currency in circulation. The stated objectives of the move were to seize undeclared income, to destroy counterfeit currency, to speed up formalization of the economy, and to increase the tax base. I find that the evidence over the subsequent three years suggests that the move had limited success in achieving its stated objectives. Disaggregated data suggests that demonetization did have appreciable costs in terms of lost jobs and output. However, the output costs appear to have been temporary.
Keywords: Monetary Systems; Standards; Regimes; Government and the Monetary System; Payment Systems